Економічна та інформаційна безпека держави: правові аспекти співвідношення - Шемчук, Віктор Вікторович; Шемчук, В. В.; Шемчук, Виктор Викторович; Shemchuk, Viktor V. (Одеса : Гельветика, 2019)
Стаття присвячена дослідженню економічної та інформаційної безпеки держави, їх теоретико-правовим, конституційно-правовим та іншим галузевим і прикладним аспектам. Проаналізовані нормативні визначення категорії «економічна безпека держави», висвітлена історія виникнення і розвитку цього терміну у міжнародно-правовій практиці. Так само як і інформаційна безпека, економічна безпека є конституційною категорією, хоча зміст їх в Основному законі не розкривається. Аналіз наукових досліджень свідчить про використання різних підходів до з’ясування сутності економічної безпеки держави. (найбільш поширеними є статичний, динамічний, системно-структурний та комплексний підходи). Єдине її нормативне визначення регламентовано у наказі Міністерства економічного розвитку та торгівлі 2013 р., засноване саме на статичному підході. В юридичній площині економічну безпеку держави можна розглядати як правовідносини, що виникають при забезпеченні органами публічної влади стану захищеності національної економічної системи. Суміжним поняттям поряд з економічною безпекою держави є інформаційна безпека країни. Останню доцільно розглядати крізь призму правовідносин, що виникають при забезпеченні стану захищеності інформаційного простору. Економічна та інформаційна безпеки різняться за об’єктом (економічна система, інформаційний простір) та засобами забезпечення. Проте, вони мають і спільні риси: йдеться про одночасне визначення складниками національної безпеки; їх забезпечення є найважливішою функцією держави; однакові рівні забезпечення (міжнародний, національний та локальний); схожі суб’єкти тощо. Економічна безпека держави, як і інформаційна безпека стали предметом вивчення різних галузей вітчизняної науки, включаючи насамперед юридичну науку. Отже, на сьогодні сформувалась їх належна доктринальна основа, проте беззаперечною є потреба вдосконалення нормативно-правової бази у сфері економічної та інформаційної безпек як складників національної безпеки України, забезпечення термінологічної визначеності, механізмів реалізації, гарантій захисту як у мирний час, так і в умовах конфліктів, гібридних воєн тощо.

Статья посвящена исследованию экономической и информационной безопасности государства, их теоретико-правовым, конституционно-правовым и другим отраслевым и прикладным аспектам. проанализированы нормативные определения категории «экономическая безопасность государства», освещена история возникновения и развитие этого термина в международно-правовой практике. Так же как и информационная безопасность, экономическая безопасность является конституционной категорией, хотя содержание их в Основном законе не раскрывается. Анализ научных исследований свидетельствует об использовании разных подходов к выяснению сущности экономической безопасности государства. (Наиболее распространены статичный, динамичный, системно-структурный и комплексный подходы). Единственное ее нормативное определение регламентировано в приказе Министерства экономического развития и торговли 2013, основано именно на статическом подходе. В юридической плоскости экономическую безопасность государства можно рассматривать как право- отношения, возникающие при обеспечении органами публичной власти состояния защищенности национальной экономической системы. Смежным понятием рядом с экономической безопасностью государства является информационная безопасность страны. Последнюю целесообразно рассматривать сквозь призму правоотношений, возникающих при обеспечении состояния защищенности информационного пространства. Экономическая и информационная безопасности различаются по объекту (экономическая система, информационное пространство) и мерами обеспечения. Однако, они имеют и общие черты: речь идет об одновременном определении составляющих национальной безопасности; их обеспечение является важнейшей функцией государства; одинаковые уровни обеспечения (международный, национальный и локальный), схожие субъекты и тому подобное. Экономическая безопасность государства, как и информационная безопасность стали предметом изучения различных отраслей отечественной науки, включая прежде всего юридическую науку. Итак, на сегодня сформировалась их надлежащая доктринальная основа, однако бесспорным является необходимость совершенствования нормативно-правовой базы в сфере экономической и информационной безопасности как составляющих национальной безопасности Украины, обеспечение терминологической определенности, механизмов реализации, гарантий защиты как в мирное время, так и в условиях конфликтов, гибридных войн и тому подобное.

The article is devoted to the study of the economic and information security of the state, their theoretical and legal aspects. The normative definitions of category «economic security of the state» are analyzed. Thus, the concept of economic security is enshrined in the Constitution of Ukraine. In particular, part 1 of Article 17 of the Constitution of Ukraine establishes that the protection of the sovereignty and territorial integrity of Ukraine, ensuring its economic and information security are the most important functions of the state, the cause of the entire Ukrainian people. At the same time, the meaning of this concept and the structure of economic security of the state as a system are not disclosed in the Basic Law. This legal category is also not analyzed in scientific and practical commentary. However, the definition of this term is contained in several by-laws, the main of which is the Methodological Recommendations for the calculation of the level of economic security of Ukraine of 2013. In order to reveal the essence of economic security, one should also refer to international legal sources, since this term has entered into domestic scientific circulation from international practice. In particular, the 40th session of the UN in 1985 adopted a resolution “International Economic Security”, which determined that economic security is a condition in which the people can independently, without pressure from outside and any intervention, determine the ways and forms its economic development. Economic security issues are constantly monitored at the UN in particular the international aspects of economic security are being analyzed as a basis for developing relations between developed and developing countries. In legal encyclopedia economic security is characterized as a state of the national economy in terms of ensuring its development and material interests of people. Such a state is achieved by a system of organizational, legal, technological and other measures of an economic nature. The analysis of scientific works shows that different approaches are used to find out the essence of economic security of the state. In this case, the most common among the authors are static, dynamic, system-structural and integrated approaches. In the legal plane, the economic security of the state can be regarded as a legal relationship that arises when the public authorities provide the state of protection of the national economic system. Economic security is linked to another component of national security, such as information security. And although they differ in object (economic system, information space) and means of security, they also share the following common features: they are national security components; their supporting is an essential function of the state; their regulation has a legal basis; have the same levels (international, states and individuals) and subjects; and serve as the primary targets in hybrid wars.
Шемчук В. В. Економічна та інформаційна безпека держави: правові аспекти співвідношення / В. В. Шемчук // Актуальні проблеми держави і права : зб. наук. пр. Вип. 83 / редкол.: Г. I. Чанишева (голов. ред.) та ін. – Одеса : Гельветика, 2019. – С. 253-259.
Keywords: економічна безпека; інформаційна безпека; гібридна війна; держава; стан економіки; ООН; экономическая безопасность; информационная безопасность; гибридная война; государство; состояние экономики; ООН; economic security; information security; hybrid war; state; economy; UN; Research Subject Categories::LAW/JURISPRUDENCE